Inovasi Pemanfaatan Budidaya Nanas, Edu-Agrowisata, Tenun ATBM, dan Kearifan Lokal Pasar Bahulak Desa Karungan, Plupuh, Sragen - Rahmawati Rahmawati; Bambang Pujiasmoro; Soenarto Soenarto; Francisca Sestri Goestjahjanti; Djuminah Djuminah; Sri Hartoko; Siti Nurlaela; Siti Arifah (Muria Jurnal Layanan Masyarakat, 2023)
This activity aims to help solve the problems faced by business actors in the development of the Pasar Bahulak tourism village in Karungan Village, Plupuh District, Sragen Regency. This activity was realized through the collaboration of UNS, UNY, and UNIPI Tangerang, in collaboration with BUMDes Sinar Karungan Mandiri, and PT KAI. The method implemented in this community service activity is the delivery of materials and assistance in empowering products from pineapple plants. The result of this activity is an increase in the knowledge and understanding of business actors in the Bahulak Market regarding the importance of the edu-agrotourism concept in empowering businesses, the concept of cost accounting, empowering pineapple plants, and creating new business networks for BUMDes Sinar Karungan Mandiri. Thus, it can further increase the level of the economy in Karungan Village, Pupuh District, Sragen Regency.